Abstracting Abstract Machines. - Danvy, Olivier; Midtgaard, Jan (Communications of the ACM, 2011)
An introduction is presented for the article "Abstracting Abstract Machines A Systematic Approach to Higher-Order Program Analysis," by David Van Horn and Matthew Might, which is published elsewhere in the same issue.